2018
DOI: 10.1364/ol.43.005230
|View full text |Cite
|
Sign up to set email alerts
|

Tunable narrowband mid-infrared thermal emitter with a bilayer cavity enhanced Tamm plasmon

Abstract: A narrowband thermal emitter exhibits higher energy efficiency and sensitivity in molecule sensing and other mid-infrared (MIR) spectral range applications compared to a blackbody emitter. Most narrowband thermal emitters involving surface plasmons have a relatively low quality factor (Q-factor) and require complex fabrication processes. Here we propose a bilayer cavity-enhanced Tamm plasmon (TP) structure with a high/low refractive index bilayer sandwiched between a metal and distributed Bragg reflector (DBR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…While both are characterized by an evanescent field that propagates along a surface, in the infrared SPPs generally possess frequency tunability and short lifetimes (broad spectral linewidths), whereas SPhPs offer limited frequency tunability and long lifetimes (narrow linewidths) [6,7] . One of the first demonstrations of spatially coherent thermal emission employed a patterned silicon carbide surface [8,9] , but such efforts have now been extended to include plasmonic structures [10][11][12] and highly dispersive dielectric resonanators [13] . Yet some of the best performance metrics achievable by periodic structures have been realized through the use of simple 1D gratings [11] or bullseye designs using metals [10] , demonstrating the potential for spectrally and spatially narrow emission.…”
Section: Introductionmentioning
confidence: 99%
“…While both are characterized by an evanescent field that propagates along a surface, in the infrared SPPs generally possess frequency tunability and short lifetimes (broad spectral linewidths), whereas SPhPs offer limited frequency tunability and long lifetimes (narrow linewidths) [6,7] . One of the first demonstrations of spatially coherent thermal emission employed a patterned silicon carbide surface [8,9] , but such efforts have now been extended to include plasmonic structures [10][11][12] and highly dispersive dielectric resonanators [13] . Yet some of the best performance metrics achievable by periodic structures have been realized through the use of simple 1D gratings [11] or bullseye designs using metals [10] , demonstrating the potential for spectrally and spatially narrow emission.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated an extraordinary absorption response from the Bi-based MPA in ultra-broadband, polarization insensitive, and almost omnidirectional NIR (near infrared) perfect absorber by using Bi nanodiscs in an metal–isolator–metal configuration 8 . The GST chalcogenide phase change materials, (this includes GeTe), can be quickly 9 and repeatedly 10 switched between amorphous and crystalline states by appropriate thermal, electric, or optical stimuli 11 13 . Until now, GST chalcogenides have been regarded as strong candidates for realizing reconfigurable and nonvolatile all-optical devices 14 , consequently, several applications have been proposed, such as all-optical switching 15 , optical filters 16 , and reconfigurable metasurfaces 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated an extraordinary absorption response from the Bi-based MPA in ultrabroadband, polarization insensitive, and almost omnidirectional NIR perfect absorber and using Bi nanodiscs in an metal-isolator-metal configuration [8]. The GST calcogenide phase change materials, (so this includes GeTe), can be quickly [9] and repeatedly [10] switched between amorphous and crystalline states by appropriate thermal, electric, or optical stimuli [11][12][13]. Until now, GST chalcogenides have been regarded as strong candidates for realizing reconfigurable and nonvolatile all-optical devices [14], and many applications have been proposed, such as all-optical switching [15], optical filter [16], and reconfigurable metasurfaces [17,18].…”
Section: Introductionmentioning
confidence: 99%